The value of money - Patnaik, Prabhat (Columbia University Press, 2009)
Why is money more valuable than the paper on which it is printed? Monetarists link the value of money to its supply and demand, believing the latter depends on the total value of the commodities it circulates. According to Prabhat Patnaik, this logic is flawed. In his view, in any nonbarter economy, the value we assign to money is determined independently of its supply and demand. Through an original and provocative critique of monetarism, Patnaik advances a revolutionary understanding of macroeconomics that highlights the "propertyist" position of Karl Marx and John Maynard Keynes. Unlike the usual division between "classical" economists (e.g., David Ricardo and Marx) and the "marginalists" (e.g., Carl Menger, William Stanley Jevons, and Léon Walras), Patnaik places "monetarists," including Ricardo, on one side, while grouping propertyist writers like Marx, Keynes, and Rosa Luxemburg on the other. This second group subscribes to the idea that the value of money is given from outside the realm of supply and demand, therefore making money a form in which wealth is held. The fact that money is held as wealth in turn gives rise to the possibility of deficiency of aggregate demand under capitalism. It is no accident that this possibility was highlighted by Marx and Keynes while going largely unrecognized by Ricardo and contemporary monetarists. At the same time, Patnaik points to a weakness in the Marx-Keynes tradition¿namely, its lack of any satisfactory explanation of why the value of money, determined from outside the realm of supply and demand, remains relatively stable over long stretches of time. The answer to this que.